The role of intrinsically disordered regions of SARS-CoV-2 nucleocapsid and non-structural protein 1 proteins - Shitaye, Getasew; Ventserova, Nataliia; D’Abrosca, Gianluca; Dragone, Martina; Maina, Eunice Wairimu; Fattorusso, Roberto; Iacovino, Rosa; Russo, Luigi; Isernia, Carla; Malgieri, Gaetano (Frontiers in Chemistry, 2025)
Virus survival inside the host cell depends on the intricate mechanisms that recruit proteins involved in the arms race. Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) proteome exhibits important levels of structural order. However, some of the SARS-CoV-2 proteins, such as the Nucleocapsid (N) and Non-structural protein 1 (Nsp1), contain a considerably significant amount of intrinsically disordered regions (IDRs) that play indispensable roles in the intra-viral and virus-host interaction. Here, focusing on proteins that contain a relevant percentage of IDRs, we discuss experimental and computational studies sought to support IDRs as a key player in the interplay with ordered domains, the biological role as potential origin for variants of SARS-CoV-2, and their association with virus transmissibility. Furthermore, we also highlight the potential involvement of IDRs in the viral-host protein interaction and host cellular machinery. Thus, shading lights on the dark proteome of the virus and looking for therapeutic approaches beyond the classic structure-function paradigm may contribute to the efforts sparking the quest for therapeutics.